Evolução das tecnologias de representação: das linguagens de marcação aos dados interligados - Martins, Paulo George Miranda (2018)
The so-called Representation Languages have always been directly related to the instruments and professional practices identified in the field of Information Science. From the development of digital technologies, the bibliographic representation formats have evolved to meet emerging information demands. In this sense, the methods of representation have always been objects of investigation in the field of Information Science that since its creation, develops methods directed to the representation of the diverse types of informational resources. In view of this scenario, we ask: what are the relations between the representation languages conventionally used in the area of Information Science and the technologies of interconnected data publishing? The objective of the research is to analyze the evolution of representation languages and to identify the existing relationships between the representation tools used in the area of Information Science and the new trends of interconnected data publication. It is a theoretical research of qualitative approach, and applied nature, focused on the analytical observation of the documents that approach the thematic of information representation. Bibliographic and documentary analysis is used as methodological procedures, addressing the volume of data and information obtained through the technique of content analysis. The research is justified due to the need for studies that corroborate for a better understanding of the new models of representation based on the proposal of interconnected data and its applications for the area of Information Science. As a result, an overview of the evolution of representation languages is presented and the main relationships with the new interrelated data publishing trends are described, especially the BIBFRAME data model.